Collaborative Learning Model to Foster Character and Multicultural Values in Madrasah Tsanawiyah Boarding Schools - Dewi, Nila Sari; Setiasih, Niti; Narimo, Sabar; Musiyam, Muhammad; Yuliani, Fatimah (Jurnal Sains Sosio Humaniora, 2025)
Islamic boarding schools (pesantren), as Islamic educational institutions, play a strategic role in shaping students' character while also developing multicultural awareness. This study aims to analyze the implementation of a collaborative learning model as a strategy for fostering character and multicultural values in pesantren at the Madrasah Tsanawiyah (MTs) level. The research method used is qualitative with a literature study and conceptual analysis approach. The findings indicate that the collaborative learning model which involves forming heterogeneous groups, assigning cooperative tasks, and emphasizing interaction and dialogue among students is effective in developing values such as tolerance, harmony, justice, brotherhood, and mutual respect for differences. The role of teachers and pesantren caregivers is crucial in designing learning activities that facilitate the internalization of these values. Challenges encountered include limited teacher training, reliance on conventional teaching methods, and diverse student group dynamics. Proposed solutions include improving teacher capacity through training, developing contextual learning materials, and conducting ongoing evaluation of the learning process and outcomes. The implications of this study emphasize the importance of integrating a collaborative approach into the pesantren curriculum to develop students who are not only academically competent but also of strong character and prepared to live in a multicultural society.